Morphology and Formation of Chrysanthemum-like Pearlite in 100Mn13 Steel During Aging Treatment - Bo Liang; Jiaoyang Sun; Zhimin Ding; Rujin Tian; Feng Yan (Crystals)
The morphology and microstructure of pearlite formed in 100Mn13 high-carbon high-manganese steel aged, respectively, at 525 °C and 650 °C after 1050 °C water toughening treatment were observed and analyzed by a scanning electron microscope (SEM) and transmission electron microscope (TEM). The results show that some pearlite colonies are chrysanthemum-like and are composed of M7C3 lamellae and ferrite lamellae, maintaining an orientation relationship (OR) of (<semantics><mover accent="true">3¯</mover></semantics><semantics>3</semantics><semantics>12</semantics>)M7C3‖(<semantics>0 <mover accent="true">2¯</mover> 4</semantics>)α, [<semantics>4 0 1</semantics>]M7C3‖[<semantics>5 2 1</semantics>]α. Moreover, the lamellae in pearlite colonies with chrysanthemum-like morphology are distributed in an emanative way, where there are protrusions and branches at the growth frontier. A growth physical model describing the growth process of chrysanthemum-like pearlite is proposed.